Paleogeography of the Southern Tarim Terrane Revealed by Neoproterozoic Mafic Dyke Swarm in Altyn - Xian‐Tao Ye; Wen‐Jun Hu; Chuan‐Lin Zhang; Wei Gan; Rui‐Chen Gao; Ming‐Can Yang (Geochemistry, Geophysics, Geosystems)
Abstract Using high‐resolution remote sensing images and detailed field investigations, this study provides the spatiotemporal distribution and geometry of the Neoproterozoic giant mafic dyke swarm in the southeastern Tarim Craton, which is crucial for reconstructing the paleogeographic position of the Tarim Craton within the Rodinia supercontinent. This dyke swarm extends over 600 km in length and 20 km in width, spanning more than 12,000 km2. Individual dykes ranged from 1.9 to 168 m in thickness and from 27 to 2,778 m in length. The mafic dykes were emplaced at 933–914 Ma, and exhibit trace element and isotope compositions similar to those of enriched mid‐ocean ridge basalts (E‐MORBs). The mantle potential temperature and pressure of the primary magma were estimated at ∼1,570°C and ∼4.0 GPa, respectively. The large‐scale dyke swarm, together with its geochemical signatures and estimated P‐T conditions, proposed that these dykes were generated by interaction between a Neoproterozoic mantle plume and the asthenospheric mantle. In addition, the Neoproterozoic giant mafic dyke swarm shares a close spatial and temporal relationship with the ∼890 Ma Sailajiazitage large igneous province in the southwestern Tarim Craton. Similar 930–890 Ma mafic dyke swarms have also been identified in North China Craton, São Francisco Craton, and Congo Craton, indicating the presence of a single giant mantle plume beneath the Rodinia supercontinent. Together with the sedimentary records and paleomagnetic data, it is proposed that the Southern Tarim Terrane was located adjacent to the São Francisco Craton and Congo Craton in the Northern Hemisphere.